2003
DOI: 10.1081/sl-120026638
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Analysis of the β System of10B18O

Abstract: Ten bands of the b system (B 2 S + À X 2 S + ) of the 10 B 18 O molecule have been observed for the first time. The spectrum was obtained by emission spectroscopy from a low-pressure arc, at medium dispersion, and vibrationally analyzed using isotope shift measurements. Vibrational analysis gave the constants o e and o e x e for both electronic states involved in the transitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Four electronic transitions give rise to BO molecular bands, viz., (a) A 2 P i / X 2 S + (A-X) transition or a-band (∼350-650 nm), (b) B 2 S + / X 2 S + (B-X) transition or b-band (∼230-330 nm), (c) C 2 P (f) / X 2 S + (C-X) transition or g-band (∼181-230 nm), and (d) B 2 S + / A 2 P i (B-A) transition or d-band (∼458-595 nm). [39][40][41] Since the a-band and the d-band overlap, theoretical simulation is challenging. The g-band, on the other hand, originates in a deep UV region, making it difficult to detect with the present detector system, which has poor quantum efficiency in the mentioned region.…”
Section: Molecular Bands Of Boron Oxide (Bo)mentioning
confidence: 99%
“…Four electronic transitions give rise to BO molecular bands, viz., (a) A 2 P i / X 2 S + (A-X) transition or a-band (∼350-650 nm), (b) B 2 S + / X 2 S + (B-X) transition or b-band (∼230-330 nm), (c) C 2 P (f) / X 2 S + (C-X) transition or g-band (∼181-230 nm), and (d) B 2 S + / A 2 P i (B-A) transition or d-band (∼458-595 nm). [39][40][41] Since the a-band and the d-band overlap, theoretical simulation is challenging. The g-band, on the other hand, originates in a deep UV region, making it difficult to detect with the present detector system, which has poor quantum efficiency in the mentioned region.…”
Section: Molecular Bands Of Boron Oxide (Bo)mentioning
confidence: 99%
“…Bojović et al reported a vibrational 16 and rotational 17 analysis of the β system of B 18 O for the first time.…”
Section: Introductionmentioning
confidence: 98%